2005
DOI: 10.1007/s10555-005-5051-5
|View full text |Cite
|
Sign up to set email alerts
|

Progression of head and neck squamous cell cancer

Abstract: Squamous cell cancer in the head and neck region (HNSC) is unique concerning its progression since it remains locoregional for long time and visceral metastases develop only in a later stage of the disease. Accordingly, molecular markers of the local invasion and the lymphatic dissemination both have critical importance. HNSC progression is associated with deregulated control of cell proliferation and apoptosis but it seems equally significant the disregulation of the proteolytic machineries. Here we outline t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…In this context, it should be taken into consideration the fact that head and neck malignancies arise in various sites, such as oral cavity and oropharynx. Thus, tumors from these different anatomic sites have distinct clinical presentations and outcomes and are associated with different risk factors and genetic characteristics, which may complicate the evaluation of potential prognostic markers (Döbrossy 2005;Tímár et al 2005). In view of above considerations, the present study aimed to focus on one anatomic site, assessing for the first time the clinical significance of PPAR-c expression in mobile tongue SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be taken into consideration the fact that head and neck malignancies arise in various sites, such as oral cavity and oropharynx. Thus, tumors from these different anatomic sites have distinct clinical presentations and outcomes and are associated with different risk factors and genetic characteristics, which may complicate the evaluation of potential prognostic markers (Döbrossy 2005;Tímár et al 2005). In view of above considerations, the present study aimed to focus on one anatomic site, assessing for the first time the clinical significance of PPAR-c expression in mobile tongue SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors from these different sites have distinct clinical presentations and outcomes, and are associated with different genetic characteristics [1]. In this study, we focused on tongue SCC (TSCC), one of the most common sites for OSCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tumors from these different sites, often invading more than one, each one with their own particular problems regarding management [3]. Also, it could be shown that various anatomic sites of oral cavity exhibit different risk factors [4] and oncogenic alterations [5] which are reflected in differences in growth pattern, clinical behavior of the tumors and prognosis. This indicates that for OSCC patients, anatomic site of the tumor is an important factor for disease outcome and treatment.…”
mentioning
confidence: 99%